Letters in the Dictionary of Ibn Jinnie Tongue of Arabs (Journal of the College of Education for Women, 2019)
We have chosen the subject of the research (the letters at Ibn Jinnie in the lexicon of the tongue of the Arabs) in order to know the opinion of Ibn Jinnie in this range of words and compare them with the opinions of scientists who preceded him to know the personality of this linguistic world.